The Antimicrobial Activity of Omiganan Alone and In Combination against Candida Isolated from Vulvovaginal Candidiasis and Bloodstream Infections - Dawid Żyrek; Andrzej Wajda; Paulina Czechowicz; Joanna Nowicka; Maciej Jaśkiewicz; Damian Neubauer; Wojciech Kamysz (MDPI AG, 2021)
Fungi from the Candida genus are widespread commensals and, at the same time, are the leading cause of fungal infections worldwide. For instance, vulvovaginal candidiasis (VVC) affects approximately 75% of women at least once in their lifetime, remaining the second most common gynecological infection. On the contrary, hospital-acquired fungal bloodstream infections (BSIs), although less frequent, are characterized by a high mortality rate. Undoubtedly, the main reason for this situation are virulence factors that these yeast-like fungi can produce, and the ability to form a biofilm is one of the most important of them. Due to the low effectiveness of classic antimycotics against Candida biofilms, an intense search for new drugs capable of eradicating this structure is highly demanded. One of the most promising groups of compounds exhibiting such properties are antimicrobial peptides (AMPs). This study focuses on a comparison of the efficacy of Omiganan and fluconazole alone and in combination against Candida strains isolated from BSIs. The obtained results are consistent with our previous reports on the effectiveness of Omiganan against clinical strains isolated from VVC. This is also the first report on the combinatory application of Omiganan in the context of fungal BSI. The majority of combinations with fluconazole showed an additive effect, as well as a synergistic effect in the range of certain concentrations. Importantly, such effects are visible at concentrations much lower than for those compounds used individually. Potentially, this entails the possibility of limiting the adverse effects (e.g., toxicity) of Omiganan and fluconazole applied in vivo, thus improving the safety profile of this particular antifungal therapy.